1992
DOI: 10.2307/2095919
|View full text |Cite
|
Sign up to set email alerts
|

Migration and the Earnings of Hispanic Men

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. This content downloaded from 128.111.121.42 on Sun, We investigate the relationship between geographic mobility and the earnings of Hispanic men and white men using the 1980 Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 8 publications
2
66
0
Order By: Relevance
“…Furthermore, according to human capital theory (Sjaastad, 1962), the decision to migrate and the returns on migration are in uenced by the labour market situation in the departure and destination regions (see also Harris and Todaro, 1970). Many studies of migration, therefore, use characteristics of the regional labour market-like unemployment rates and wage rates-as explanatory variables (for example, Tienda and Wilson, 1992;Newbold, 1996;Shumway and Hall, 1996). In this study, the size of the place of residence is measured according to three categories: , 20 000 inhabitants, 20 000-100 000 inhabitants and .…”
Section: Other Variablesmentioning
confidence: 99%
“…Furthermore, according to human capital theory (Sjaastad, 1962), the decision to migrate and the returns on migration are in uenced by the labour market situation in the departure and destination regions (see also Harris and Todaro, 1970). Many studies of migration, therefore, use characteristics of the regional labour market-like unemployment rates and wage rates-as explanatory variables (for example, Tienda and Wilson, 1992;Newbold, 1996;Shumway and Hall, 1996). In this study, the size of the place of residence is measured according to three categories: , 20 000 inhabitants, 20 000-100 000 inhabitants and .…”
Section: Other Variablesmentioning
confidence: 99%
“…c An individual is at least in the one of the following ®ve criteria, then the individual is excluded from the sample. Although our sample may still have certain limitations,4 we attempted to minimize many of the problems that existing studies (Cooke and Bailey 1996;Cushing 1993;Tienda and Wilson 1992) have ignored. Moreover, since there minimal di¨erence in the sample size between independent and linked migrants, our regression results are not a¨ected by sample di¨erences.…”
Section: Data and Sampling Processesmentioning
confidence: 99%
“…The national origin differences Borjas finds in returns to human capital may be due to some unobservable individual characteristic that is a measure of "quality", or it may be due to some group level characteristics, such as the effects of ethnic networks on economic incorporation, or discrimination in the form of hiring queues, lesser pay for equal work, or some other sort of differential reaction on the part of American society based on something other than individual characteristics. Lieberson (1980) showed that greater concentrations of partic ular ethnic groups in a particular labor market increased the chances for competition and discrimination against those groups (see also Tienda & Wilson 1992). Later cohorts by definition face greater concentrations of their group as they join earlier migrants from their ethnic groups.…”
Section: New Immigrants and Native Minoritiesmentioning
confidence: 99%